(untitled) (Scientific journal of the Fergana State University, 2023)
The basic requirements imposed on medical workers today primarily imply solutions to such tasks as the development of professional competence, as well as full compliance with the requirements of world standards. At the same time, it is expected to achieve such results as the development of literacy in English relying on the priorities of educational policy, further development of intellectual potential based on modern standards. In addition, in the process of globalization, the appearance of English as an important aspect of professional training and the desire to find a suitable and correct learning strategy for themselves in the process of solving relevant problems, the integration of communicative medical English as a science in medical higher education is interpreted within the framework of a set of effective methods based on the point of view of training modern and in-demand personnel.